The Emrek vs Sabranovic case: an economic analysis of the consumer’s jurisdiction rule for the European Union - Teixeira Júnior, José Borges (Civil Procedure Review, 2019)
The paternalism of the procedural law can have unthinkable results. This paper address exactly to this topic, analyzing a ruling made by the European Court of Justice regarding the competence of a EU country to adjudicate a case between two parties, the consumer and the company, in which the said objective of the adjudication as it was made was to protect the consumers. This paper tries to show how it could go wrong, by deriving a model of the behavior of companies and consumers after the ruling was made.